Auditor Rotation and Financial Reporting: A Moderating Role of Corporate Governance in Nigeria - Kwaghkule, Philip; Jackson-Akhigbe, Beauty E.; Abusomwan, Rachael E. (Archives of Business Research, 2025)
The purpose of this research paper was to examine the moderating effect of corporate governance on the relationship between auditor change and financial reporting in Nigeria. The study sample six (6) listed health and pharmaceutical Companies in the Nigerian Exchange Group (NGX) for the period of 2012 to 2023. The data were analysed using descriptive statistics, correlation analysis and least square regression technique. The results shows that auditor rotation exerted a positive and insignificant effect on financial reporting, audit fees exerted a negative and significant effect on financial reporting at 1% level of significance while the moderating effect between auditor rotation and corporate governance on financial reporting was positive and insignificant. The study recommended that relevant stakeholders of health and pharmaceutical companies should ensure that there is frequency of auditor rotation towards improving financial reporting overtime, and management should comply with the corporate governance code of conduct for ensuring quality financial reporting.